An hypothesis on the early evolution of the development of the isocortex. - Aboitiz, F; Montiel, J; López, J (2002)
We propose an hypothesis on the evolutionary origin of the unique inside-out developmental gradient of the isocortex, in which deep layers originate before superficial layers. This contrasts with the development of the reptilian cortex, which originates in an outside-in gradient. In mice, a mutated protein, reelin, produces the reeler phenotype, whose cortex has an outside-in neurogenetic gradient like in reptiles. Reelin is normally located in the marginal layer of the developing cerebral cortex, and its normal function has been proposed to be a stop signal that prevents radially migrating cells from moving into the marginal zone. Additionally, mutations on the kinase Cdk5, or in its neuronal-specific activator p35, produce a deficit similar to reeler in that the neurogenetic gradient is outside-in. However, contrary to reeler, in which no cell-sparse layer I is observed, in these mice, a well-defined layer I exists, which suggests that migrating cells respond normally to reelin. Apparently, Cdk5/p35 participate in permitting cortical cells to move across pre-existing (earlier produced) cortical layers, in order to be able to contact reelin once they reach the marginal zone. We suggest that the evolutionary advent of the mammalian cortical inside-out gradient became partly possible through the activation of the Cdk5/p35 pathway, which permitted migrating cells to move across layers of older cells. At about the same time, reelin became an important element in cortical development as it prevented neuronal migration into the marginal zone (cortical layer I) and facilitated the migration of neurons past postmigratory elements.